On the Minskyan business cycle - Korkut A. Ertürk (Levy Economics Institute of Bard College, 2006)
The essential insight Minsky drew from Keynes was that optimistic expectations about the future create a margin, reflected in higher asset prices, which makes it possible for borrowers to access finance in the present. In other words, the capitalized expected future earnings work as the collateral against which firms can borrow in financial markets or from banks. But, then, the value of long-lived assets cannot be assessed on any firm basis, as they are highly sensitive to the degree of confidence that markets have about certain events and circumstances that will unfold in the future. This means that any sustained shortfall in economic performance in relation to the level of expectations that are already capitalized in asset prices may promote the view that asset prices are excessive. Once the view that asset prices are excessive takes hold in financial markets, higher asset prices cease to be a stimulant. Initially debt-led, the economy becomes debt-burdened. In this article, it is argued that Keynes's views on the alternation of the "bull" and "bear" sentiment and asset price speculation over the business cycle can explain two of Minsky's central propositions relative to business cycle turning points that have often been found less than fully persuasive: (1) that financial fragility increases gradually over the expansion, and, (2) that the interest rate sooner or later, increases setting off a downward spiral bringing the expansion to an end.
Keywords: B22; E12; E44; 330; Minsky; two-price theory; financial fragility